2020
DOI: 10.17146/aij.2020.835
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Structure Analysis of Prepared Mesoporous Silica Using Small Angle X-Ray Scattering

Abstract: Ordered pores structure analysis of mesoporous silica materials using a template of poly(ethylene oxyde)-poly(propylene oxide)-poly(ethylene oxide), PEO-PPO-PEO, triblock copolymer or Pluronics in numerous synthesis conditions has been conducted. Two different length of hydrophilic chain of Pluronics, i.e., P123 (EO 20 PO 70 EO 20) and F127 (EO 106 PO 70 EO 106), produced two different fine pore structures, which were basically hexagonal and cubic. A highly ordered pore structure, confirming with many Bragg pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Previous research has been conducted to study the properties of the MSN nanostructures using small-angle X-ray scattering (SAXS) and one of the applications for radioactive drug delivery. 16,17 From the SAXS characterization study on SBA-16-Al which was carried out previously, it was observed that the synthesized SBA-16-Al is an MSN that has pores in the uniform mesoporous order, a threedimensional cubic Im3m structure, and has a high specic surface area, up to 1000 m 2 g −1 . Mesoporous silica nanomaterial with a high specic surface area and large pore volume will provide a high drug-loading capacity, 18,19 thus lowering the frequency of drug administration.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has been conducted to study the properties of the MSN nanostructures using small-angle X-ray scattering (SAXS) and one of the applications for radioactive drug delivery. 16,17 From the SAXS characterization study on SBA-16-Al which was carried out previously, it was observed that the synthesized SBA-16-Al is an MSN that has pores in the uniform mesoporous order, a threedimensional cubic Im3m structure, and has a high specic surface area, up to 1000 m 2 g −1 . Mesoporous silica nanomaterial with a high specic surface area and large pore volume will provide a high drug-loading capacity, 18,19 thus lowering the frequency of drug administration.…”
Section: Introductionmentioning
confidence: 99%